Macrobiotus polonicus, a new species of Tardigrada from Poland (Eutardigrada: Macrobiotidae, ‘hufelandi group’) - Pilato, Giovanni; Kaczmarek, Łukasz; Michalczyk, Łukasz; Lisi, Oscar (Zootaxa, 2003)
A new species of the ‘Macrobiotus hufelandi group’, Macrobiotus polonicus sp. nov., is described from Poland. It is very similar to M. persimilis Binda & Pilato, 1972 but differs from it by having two characteristic lateral gibbosities on the hind legs, a narrower buccal tube, more slender claws, less developed lunules of the hind legs with less evident marginal indentations and eggs with fewer processes slightly different in shape.